Deregulated Long Non-Coding RNA HCG11 in Cerebral Atherosclerosis Serves as a Biomarker to Predict the Risk of Cerebrovascular Events - Juan Du MD; Lingling Wang MD; Cunling Lv MD (Clinical and Applied Thrombosis/Hemostasis, 2023)
Carotid artery stenosis (CAS) is one of the main risk factors of ischemic stroke (IS), which needs a screening and monitoring biomarker. The study focused on the clinical significance of long non-coding RNA (lncRNA) HCG11 in CAS patients aiming to identify a potential therapeutic target for CAS. Serum samples were collected from 70 CAS patients and 80 age- and gender-matched healthy people. HCG11 levels were measured via quantitative real-time PCR (qRT-PCR), and its significance in CAS identification and development prediction was also assessed. HCG11 was enriched in the serum of CAS patients, and serves as a possible biomarker for disease diagnosis with the area under the curve (AUC) of 0.930. Elevated expression of HCG11 was significantly correlated with hypertension, dyslipidemia, and degree of carotid stenosis. HCG11 was highly expressed in severe CAS cases compared to moderate ones, which was positively related to the disease severity. Cox regression analysis determined the close relationship of serum HCG11 with the occurrence of cerebral ischemia events. CAS patients with high HCG11 expression showed a high occurrence rate of cerebral ischemia events. The upregulation of HCG11 could serve as a potential diagnostic biomarker for CAS and is positively related to the disease severity. Serum HCG11 can independently predict the occurrence of following cerebral ischemia events.